2022
DOI: 10.3934/mbe.2022119
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of therapeutic neural stem cell migration in mouse brain with and without brain tumors

Abstract: <abstract><p>Neural stem cells (NSCs) offer a potential solution to treating brain tumors. This is because NSCs can circumvent the blood-brain barrier and migrate to areas of damage in the central nervous system, including tumors, stroke, and wound injuries. However, for successful clinical application of NSC treatment, a sufficient number of viable cells must reach the diseased or damaged area(s) in the brain, and evidence suggests that it may be affected by the paths the NSCs take through the bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
0
1
0
Order By: Relevance
“…Our simulation revealed that diffusion-like migration is sufficient to populate HVC and nearby regions with new neurons across biologically relevant timescales. This generative model is part of a growing class of quantitative models that simulate cellular dynamics and pattern formation in tissue development [70][71][72][73][74] , including neuronal migration [75][76][77][78] .…”
Section: Simulation Predicts Existence Of Multiple Forms Of Migrationmentioning
confidence: 99%
“…Our simulation revealed that diffusion-like migration is sufficient to populate HVC and nearby regions with new neurons across biologically relevant timescales. This generative model is part of a growing class of quantitative models that simulate cellular dynamics and pattern formation in tissue development [70][71][72][73][74] , including neuronal migration [75][76][77][78] .…”
Section: Simulation Predicts Existence Of Multiple Forms Of Migrationmentioning
confidence: 99%
“…When working with cross-sectional images, one of the most complex problems is segmenting out some specific tissues. Segmentation helps doctors more accurately locate the lesion and assess the severity of the lesion, and is an essential and critical process in disease treatment [ 1 ]. Manual localization and segmentation of tumor regions by physicians is an expensive, time-consuming, and tedious task, and the segmentation results are not reproducible.…”
Section: Introductionmentioning
confidence: 99%